At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
x = - 7, y = 6
Step-by-step explanation:
7x + 7y = - 7 -----> equation 1
- 10x - 7y = 28 -----> equation 2
Add equations 1 & 2,
7x + 7y = - 7
- 10x - 7y = 28
___________
- 3x + 0 = 21
- 3x = 21
x = 21 / - 3
x = - 7
Substitute x = - 7 in equation 1,
7x + 7y = - 7
7y + 7x = - 7
7y + 7 ( - 7 ) = - 7
7y - 49 = - 7
7y = - 7 + 49
7y = 42
y = 42 / 7
y = 6
Answer:
x = -7
y = 6
Step-by-step explanation:
7x + 7y = -7 ------------------(I)
-10x - 7y = 28 ----------------(II)
Add both the equation and so y will be eliminated and we can find the value of x
(I) 7x + 7y = -7
(II) -10x - 7y = 28 {Now add}
-3x = 21 {Divide both sides by (-3)}
x = 21/-3
x = -7
Plugin x = -7 in equation (I)
7*(-7) + 7y = -7
-49 + 7y = -7
7y = -7 + 49
7y = 42
y = 42/7
y = 6
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.